1984
DOI: 10.1139/z84-306
|View full text |Cite
|
Sign up to set email alerts
|

Echolocation and foraging behaviour in the Hawaiian hoary bat, Lasiurus cinereus semotus

Abstract: Free-flying individual Lasiurus cinereus semotus were observed as they foraged near incandescent lights on the island of Kauai, Hawaii. Two types of vocalizations were recorded from the bats: an echolocation–hunting signal with peak frequency of 27.8 kHz and an agonistic social signal, emitted while the bats were in aggressive pursuit of one another, with a peak frequency of 9.6 kHz. The tendency to vocalize agonistically increased with increased numbers of bats in the foraging area and increased as the densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 26 publications
4
68
2
Order By: Relevance
“…in the 'honking behaviour' of Noctilio leporinus on a collision course (Suthers 1965). Evidence of acoustic communication between foraging T. teniotis comes from our occasional observation of mixtures of echolocation calls and distinct low-frequency social calls (see also Belwood & Fullard 1984;Fenton 1985;Racey & Swift 1985), and also from the 'social buzzes' that were observed only in multi-bat situations, not when bats flew alone ( figure 1c(ii)). …”
Section: Discussionmentioning
confidence: 95%
“…in the 'honking behaviour' of Noctilio leporinus on a collision course (Suthers 1965). Evidence of acoustic communication between foraging T. teniotis comes from our occasional observation of mixtures of echolocation calls and distinct low-frequency social calls (see also Belwood & Fullard 1984;Fenton 1985;Racey & Swift 1985), and also from the 'social buzzes' that were observed only in multi-bat situations, not when bats flew alone ( figure 1c(ii)). …”
Section: Discussionmentioning
confidence: 95%
“…Other studies have also shown high foraging activity around lights by hoary, red and big brown bats (Wilson 1965, Hamilton and Whitaker 1979, Fenton et al 1983, Belwood and Fullard 1984, Geggie and Fenton 1985, Barclay 1985, Furlonger et al 1987, Fullard 1989; therefore, lights on turbines may increase the probability of bat collisions, assuming that the Federal Aviation Administration lighting attracts nocturnal insects. At Buffalo Ridge (MN) Phase III site, however, 42 (48%) of the 87 bat fatalities were found at lighted turbines and 45 (52%) were found at unlit turbines, and approximately half of the turbines sampled were lighted, suggesting that presence of lighting had no bearing on numbers of collision fatalities at that site.…”
Section: Department Of Energy 2002)mentioning
confidence: 97%
“…Surprisingly, studies with captive bats have shown that they can avoid colliding with moving objects more successfully than stationary ones, presumably because their foraging habits program them to detect moving objects (Jen and McCarty 1978). It seems unlikely that foraging bats using echolocation to locate prey would be unable to detect the turbines, especially given the hoary bat's ability to detect prey at long distances (Simmons and Stein 1980, Belwood and Fullard 1984, Barclay 1985, Barclay 1986). As evidence that foraging bats can detect turbines, bats were observed foraging within 1 meter of an operating wind turbine in Europe, yet no mortality was documented (Bach et al 1999).…”
Section: Bat Mortality and Use At Wind Plantsmentioning
confidence: 99%
“…Bats have been observed foraging around lights ever since artificial lighting became pervasive (Shields and Bildstein 1979;Belwood and Fullard 1984;Barak and Yom-Tov 1989;Acharya and Fenton 1999). Artificial light attracts many positively phototactic insects (Rydell 1992;Eisenbeis 2006), and most insectivorous bats are probably opportunistic feeders.…”
Section: Observational Studies On Bats At Street Lightsmentioning
confidence: 99%